(untitled) (Nigerian Dental Journal, 2026)
Background: Root canal treatment (RCT) is a cornerstone of restorative dental practice, and the choice of instrumentation system may influence clinical outcomes. Despite global advances in rotary nickel-titanium (NiTi) technology, manual instrumentation persists in many resource-constrained teaching environments. This study evaluated the types of instrumentation and techniques used in RCT across different caregiver designations at a tertiary teaching hospital in Nigeria. Methods: A retrospective cross-sectional study was conducted involving 357 RCT cases performed at University College Hospital, Ibadan, from January 2020 to December 2022. Data were extracted from standardized endodontic records using a structured form. Variables included caregiver designation (resident, house officer, consultant, student), instrumentation type (manual, rotary, combined), and technique (step-back or crown-down). The association between caregiver designation and instrumentation type was assessed using chi-square analysis, with significance set at p ≤ 0.05. Results: Residents performed the majority of procedures (88.2%). Manual instrumentation was used in 353 cases (98.9%), while rotary and combined techniques were each used in 2 cases (0.6%). The step-back technique predominated (97.8%). A statistically significant association was found between caregiver designation and instrumentation type (p < 0.001). Conclusion: Manual instrumentation remains overwhelmingly dominant at this teaching hospital, with rotary NiTi systems confined to more experienced clinicians. Targeted strategies to integrate rotary instrumentation into undergraduate and postgraduate curricula are urgently needed. Keywords: Root canal treatment; rotary instrumentation; nickel titanium; manual instrumentation; caregiver designation; endodontics; Nigeria